2021
DOI: 10.26717/bjstr.2021.34.005552
|View full text |Cite
|
Sign up to set email alerts
|

"In Vitro: Natural Compounds (Thymol, Carvacrol, Hesperidine, and Thymoquinone) against Sars-Cov2 Strain Isolated from Egypt"

Abstract: Background: The current pandemic of the coronavirus disease-2019 (COVID-19) has badly affected our life during the year 2020. SARS-CoV-2 is the primary causative agent of the newly emerged pandemic. Natural flavonoids, Terpenoid and Thymoquinone are tested against different viral and host-cell protein targets. These natural compounds have a good history in treating Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV). Methods: Molecular docking combined with cytotoxicity and plaque reduction assay is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The concentration‐dependent cytotoxic effect of natural compounds, including thymol (617 μM), CAR (464 μM), hesperidin (5.58 μM), and thymoquinone (3.9 μM) on Vero E6 cell line has been shown. In addition, CAR, hesperidin, and thymoquinone showed comparable binding affinities (−7.0, −6.9, and − 6.9 kcal/mol, respectively) to SARS‐CoV‐2 Mpro with that of the standard compound (−7.2 kcal/mol) in molecular docking study 64 . The molecular interactions between mono‐terpenoids, including carvon, CAR, and thymol and spike protein of SARS‐CoV‐2 together with the cellular proteases TMPRSS2, cathepsin B (CatB), and cathepsin L (CatL) showed that the mono‐terpenoids has most effective molecule against all targets, which inhibited entry of the virus to the host cells 65 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The concentration‐dependent cytotoxic effect of natural compounds, including thymol (617 μM), CAR (464 μM), hesperidin (5.58 μM), and thymoquinone (3.9 μM) on Vero E6 cell line has been shown. In addition, CAR, hesperidin, and thymoquinone showed comparable binding affinities (−7.0, −6.9, and − 6.9 kcal/mol, respectively) to SARS‐CoV‐2 Mpro with that of the standard compound (−7.2 kcal/mol) in molecular docking study 64 . The molecular interactions between mono‐terpenoids, including carvon, CAR, and thymol and spike protein of SARS‐CoV‐2 together with the cellular proteases TMPRSS2, cathepsin B (CatB), and cathepsin L (CatL) showed that the mono‐terpenoids has most effective molecule against all targets, which inhibited entry of the virus to the host cells 65 .…”
Section: Resultsmentioning
confidence: 81%
“…In addition, CAR, hesperidin, and thymoquinone showed comparable binding affinities (À7.0, À6.9, and À 6.9 kcal/ mol, respectively) to SARS-CoV-2 Mpro with that of the standard compound (À7.2 kcal/mol) in molecular docking study. 64 The molecular interactions between monoterpenoids, including carvon, CAR, and thymol and spike protein of SARS-CoV-2 together with the cellular proteases TMPRSS2, cathepsin B (CatB), and cathepsin L F I G U R E 4 Preventive effects of carvacrol on paraquat (PQ) induced toxicity. CAT, catalase; GPx, glutathione peroxidase; GSH, glutathione; MAPK, mitogen-activated protein kinase; MDA; malondialdehyde; ROS, reactive oxygen species; SOD, superoxide dismutase; ΔΨm, mitochondrial membrane potential.…”
Section: The Effect Of Car On Lung Cancer and Lung Infectionsmentioning
confidence: 99%
“…Accordingly, a recent study has shown that administration of Nigella sativa L. (black cumin) over 2 weeks reduces the severity of COVID-19 symptoms and elicited viral clearance [ 159 ]. The active compound in N. sativa seems to be thymoquinone, which shows high efficacy against SARS-CoV-2 according to recently published findings [ 160 , 161 ]. The link to TRP channels is provided by yet another study, which finds that N. sativa also affects the expression of TRP channels [ 162 ].…”
Section: Emerging Treatment Strategiesmentioning
confidence: 85%
“…Some in vitro studies investigated the antiviral activity of flavonoids in combating SARS-CoV [64] [82] and SARS-CoV2 [83] [84] [85] [86] infection. Hesperetin, Luteolin, and Apigenin have been demonstrated as potent inhibitors of SARS-CoV-2 3CLpro in vitro and can be considered proper candidates for further optimization and development of therapeutic interventions, particularly those related to inflammation processes and immunity [86].…”
Section: Discussionmentioning
confidence: 99%